Screening for angiotensin I-converting enzyme (ACE) inhibitory activity of enzymatic hydrolysates obtained from Azorean macroalgae - Paiva, Lisete S. (2016)
As part of ongoing studies into the isolation of antihypertensive peptides, 12 common macroalgae species from Azores were investigated for their potential angiotensinconverting enzyme (ACE) inhibitory properties. After optimization of enzymatic hydrolysis conditions, the anti-ACE activity was determined by high performance liquid chromatography (HPLC). The species under study include four Rhodophyta (Gelidium microdon, Osmundea pinnatifida, Porphyra sp. and Pterocladiella capillacea), four Chlorophyta (Chaetomorpha linum, Codium adhaerens, Ulva compressa and Ulva rigida) and four Heterokontophyta (Cystoseira humilis, Fucus spiralis, Padina pavonica and Sargassum cymosum). The bromelain hydrolysates derived from P. capillacea, Porphyra sp., F. spiralis, U. compressa, O. pinnatifida and U. rigida were the most active presenting an ACE inhibitory activity of 48.73 ± 1.58%, 50.96 ± 1.82%, 56.77 ± 1.80%, 59.80 ± 0.95%, 62.59 ± 1.60% and 65.68 ± 0.72%, respectively. These results suggest that some macroalgae from the littoral Azorean sea are potential sources of powerful ACE inhibitor peptides, with potential impact on public health, particularly on the hypertensive patients. These features make these algae valuable to the regional economy and may also provide an incentive for marine biodiversity conservation and valuation of marine algal resources.